Prediction on water quality of point source pollution for Lunchoo River, Johor [electronic resource] - Rafidah Shahperi, 1984-; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Kejuruteraan (Awam - Hidraul dan Hidrologi)) - Universiti Teknologi Malaysia, 2010